MODEL PEMBELAJARAN TOLAK PELURU BERBASIS MEDIA PADA SISWA SMP - Ahmad Rifai; Iwan Setiawan; Rizky Nurulfa (Jurnal Speed (Sport, Physical Education, Empowerment), 2022)
This research aims to produce a media-based bullet repellent learning model product in junior high school students that can be applied in the learning process, this research is expected to help teachers during the physical education learning process, especially in the material in the bullet repellent number. This research uses the ADDIE method, in the ADDIE model research there are 5 stages of research processes, namely Analysis, Design, Model Development, Implementation, Evaluation. The results of the study produced a product in the form of a media-based bullet repellent learning model for junior high school students that has been validated and revised by athletic experts, learning experts and learning media experts as many as 22 models. The data collection technique by distributing questionnaires to sample students at SMP Negeri 158 schools about the attractiveness of the model and the ease of the media made data analysis is carried out descriptively. The results of the study were in the form of a mediabased bulletproof learning model book for junior high school students. Based on the results of the study, it is proven that the media-based bullet repellent learning model in junior high school students has been declared feasible / valid and can be applied to junior high school students by athletic experts, learning experts and learning media experts.Keywords : Learning model, shot put, learning media